Sufi Dance in the Context of Indonesian Islamic Culture: Art Learning Strategies for Preserving Aesthetics and Spiritual Meaning - Imrotul Afifah; Hartono Hartono (Universitas Muhammadiyah Enrekang, 2025)
The purpose of this study is to analyze and examine Sufi dance within the context of Islamic culture, focusing on the integration of aesthetics and spirituality in the adaptation of Sufi dance in the Indonesian archipelago, as well as the interpretation of meanings embedded in the signs of Sufi dance movements. This research employs a qualitative approach combined with Roland Barthes’ semiotic analysis method. The data and sources consist of primary data (Sufi dance pioneers, instructors, dancers, and audiences or congregations who witness Sufi dance) and secondary data derived from documents or historical records of Sufi events in the archipelago, as well as scholarly articles related to Sufi dance. Data collection techniques include in-depth interviews, participant observation, document studies, and life history analysis. Data analysis involves an in-depth exploration of how meanings in various movements are conveyed through signs found in archives, historical records, and historical events. The analysis also investigates how the integration between aesthetics and spirituality in Sufi dance can create a dynamic interplay within the values of Islamic culture in the archipelago. The findings reveal that Sufi dance is a sacred performance that embodies spiritual values in every movement, with symbolic meanings deeply rooted in religious contexts. The counterclockwise spinning movement, which serves as the core gesture of Sufi dance, symbolizes the rotation of the Earth and the tawaf around the Kaaba. Various meaningful movements in Sufi dance, analyzed through denotative and connotative interpretations, conclude that these movements represent the meaning of human life both physically and metaphysically. Moreover, they illustrate how aesthetics and spirituality interact in the context of Islamic culture in the Indonesian archipelago, resulting in a Sufi dance style that incorporates improvisation and adaptation from its cultural origins.